RANCANG BANGUN SISTEM E-COMMERCE PADA PT KARTIKA UTAMA INTI - Tri Driano, Welly; Rika Harman (Computer Science and Industrial Engineering, 2024)
This research focuses on designing an e-commerce platform for PT. Kartika Utama Inti, located in Batu Ampar, Batam City, Riau Islands, which experiences increasing visits every year. E-commerce has become one of the main platforms for companies to expand their market reach and increase sales. The aim of this research is to design an e-commerce platform for PT Kartika Utama Inti using the waterfall method. The waterfall method is chosen because it provides a structured and sequential approach to software development. This research begins with an analysis of user and business needs, which are then used as the basis for designing a suitable e-commerce system. The next stages include system design, implementation, testing, and maintenance. The development process is carried out gradually and linearly, allowing for good control over each stage of development. The waterfall method also facilitates comprehensive documentation, which serves as a guide for future system development and maintenance. The results of this research are expected to provide guidance for PT Kartika Utama Inti in effectively and efficiently developing and maintaining their e-commerce platform.